PENATALAKSANAAN PADA WANITA USIA 76 TAHUN DENGAN OSTEOARTHRITIS DAN DISPEPSIA MELALUI PENDEKATAN KEDOKTERAN KELUARGA - Dhea Oksalia Edi (Journal of Health Science and Physiotherapy, 2022)
Background: Osteoarthritis (OA) is a degenerative disease of the joints characterized by damage to joint cartilage and subchondral bone that causes joint pain. In Indonesia, OA is the most common rheumatic disease in the community. Dyspepsia is a digestive disorder that refers to a collection of symptoms such as a painful or uncomfortable sensation in the stomach, nausea, vomiting, fullness and bloating. Purpose: Applying evidence-based medicine (EBM)-based family doctor services based on a patient problem solving framework with a family approached and patient centered approach. Method: Primary data were obtained through history taking, physical examination and home visits to complete family data, psychosocial and environmental data. Assessment is carried out based on a holistic diagnosis from the beginning, process, and end of the study quantitatively and qualitatively. Results: Patient Mrs. S, 76 years old, complained of pain in both knees and a burning feeling in the stomach.The patient was diagnosed as osteoarthritis and functional dyspepsia. In this case, the diagnosis and treatment have been carried out according to the theory and related journals. After the intervention, there was a decrease in clinical symptoms and an increase in patient and family knowledge. Conclusion: Holistic management can improve knowledge, attitudes, and behavior in patients. In addition, the role of the family is very important in the care and treatment of patients and support is also needed